The Influence Of Social Media On Mental Health And Physical Of Adolescent Athletes : A Systematic Review - Prasetya, Muhammad Reza Aziz; Chow, Hsueh Wen (Indonesian Journal of Kinanthropology (IJOK), 2023)
Background: Mobiles have become an essential tool in today's world as many activities can be conducted online. According to a 2015 study, over 2,000 adolescents use mobile phones to access social media for 92% of their day. However, the excessive use of social media can have negative impacts on the mental and physical health of adolescent athletes, such as increased stress, unhealthy lifestyle habits (such as alcohol and drug use), changes in sleep patterns, and obesity. It is therefore crucial for adolescent athletes to manage their time on social media in order to maintain their mental and physical health. This study aims to explore the relationship between social media usage and the mental and physical health of adolescent athletes. Methods: In this study, the researcher employed a systematic review method and selected articles using the PRISMA method. The articles were retrieved from online databases such as Google Scholar and ScienceDirect. The articles used in the study were published between 2017 and 2022 (a period of 5 years). Results: Based on the five selected articles, it was found that all of them reported a correlation between social media usage and the mental and physical health of adolescent athletes. Conclusions: Therefore, it can be concluded that better time management of social media usage can have a positive impact on the mental and physical health of adolescent athletes.